Mechanism of Establishment of Joint Venture between PT. Pelindo With PT. Inalum - Lubis, Arif Maulana; Sahputra, Rilawadi; Kusbianto, Kusbianto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
The purpose of this study was to determine the mechanism of formation of joint venture between PT Pelindo and PT Indonesia Asahan Alumunium (PT. Inalum), as well as the legal position of PT Prima Regional Development according to Presidential Regulation Number 81 of 2018 concerning the acceleration of the development and operation of the Kuala Tanjung Port and Industrial Estate in North Sumatra province. This research is included in descriptive research with normative juridical research using qualitative data analysis methods. Research methods used empirical juridical research methods, the results showed that PT Pelindo (Persero) must acquire shares owned by PT PMT in PT PPK by 10% so that at the time of joining PT Inalum to form a joint venture entity, the position of PT Pelindo (Persero) is a 100% shareholder of PT PPK. Later, if PT Inalum conducts capital participation, PT Inalum can buy part of PT PPK shares from PT Pelindo (Persero) so that the composition of PT PPK shareholders is PT Pelindo (Persero) and PT Inalum.